A new species of Centruroides Marx (Scorpiones: Buthidae) from Panama and new distribution records for Centruroides bicolor (Pocock, 1898) and Centruroides granosus (Thorell, 1876) - Arias, Diomedes Quintero; Esposito, Lauren A. (Zootaxa, 2014)
A new species, Centruroides panamensis n. sp., from the foothills of Volcán Barú in the Province of Chiriquí, Panama is described with a extremely narrow distributional range. New distribution records of Centruroides bicolor (Pocock, 1898) are also presented.